The Effect of Media Exposure on Participation in Demonstrations Regarding the Constitutional Court Ruling (A Survey Study of Students in Surabaya) - Isna, Winna Lailatul; Aurelia, Chelsea; Kotifah, Firda (International Journal of Communication, Media, and Development Studies, 2024)
This research aims to determine the influence of media exposure on the participation of Surabaya students in demonstration actions related to the Constitutional Court’s decision. (MK). This study uses a quantitative approach with a survey method involving 399 student respondents selected using the Slovin formula. The main data collection instrument was a questionnaire with a Likert scale, which was tested for validity and reliability. The research variables include media exposure (frequency, duration, attention) as the independent variable and participation in demonstration actions (type of participation, motivation, impact) as the dependent variable. The analysis results show a significant relationship between media exposure and student participation in demonstration actions. The Pearson correlation test yielded a value of 0.614, indicating a strong relationship, while the regression test showed that 40.5% of the action participation variable could be explained by media exposure. Social media, as a form of new media, plays a crucial role in disseminating information and mobilizing the masses through features such as hashtags, retweets, and online campaigns. This research concludes that media exposure, particularly social media, has a significant impact on student action participation, both directly and indirectly. The results show that media exposure, especially through social media, has a significant influence on student participation. High frequency of media information consumption is positively correlated with student involvement in demonstrations. Social media proved to be the main platform for information dissemination and mass mobilization. In addition, emotional media content, such as videos and images, are able to increase students’ emotional engagement and motivate their participation.